Pengaruh Penggunaan Media Pembelajaran Cisco Webex Terhadap Hasil Belajar Siswa pada Mata Pelajaran TIK Kelas XI di SMAN 2 Mandau - Hasanah, Nurfadillatul; Zakir, Supratman (ANTHOR: Education and Learning Journal, 2023)
This research is motivated by the problems that occurred when the covid-19 pandemic attacked Indonesia. Schools were transferred to study at home during covid-19 by the government to prevent transmission of the covid-19 virus. The purpose of this study was to determine the difference in student learning outcomes by using cisco Webex learning media and without using cisco Webex learning media in class XI ICT subjects at SMAN 2 Mandau. Respondents or samples in this study were class XI MIPA 1 and class XI MIPA 2. With the type of experimental research with the research design True experimental design and the type of research, the design used a Posttest-only Control group design. The technique in sampling is purposive sampling. Purposive sampling is a sampling technique thatresearchers consider when taking samples. After research from all the tests that have been carried out and the results are the effect of using cisco Webex learning media can improve student learning outcomes in the experimental class the hypothesis is proven by statistical analysis which states that the sig value < α is 0.000 ≤ 0.05 which states that H0 is rejected and Ha is accepted and the T Count value is 8.078 and the table value with degree N-2 (50-2 = 48) the value of dk (0.05) = 2,021. So, t.count ≥ T table (8.078 ≥ 2.021) indicates that the null hypothesis (H0) is rejected and the alternative hypothesis (Ha) is accepted. Andaccording to the hypothesis test conducted, there is a significant difference in the learning outcomes of class XI students in ICT subjects at SMAN 2 Mandau between those using cisco Webex learning media and those who do not use cisco Webex learning media.